PERANCANGAN KAPAL PETI KEMAS 7200 DWT DENGAN KECEPATAN 7200 KNOT UNTUK RUTE PELAYARAN MALAHAYATI - TANJUNG PRIOK - Muna 'Afifah, (2021)
Along with the progress and development of science and technology, an effective and efficient system for the transportation of goods by sea, namely with container systems. The existence of this container system then the transportation of goods by sea is more useful so that what consumers expect can be realized, namely cost and time saving, guaranteed security and more load. Therefore container systems become one of the main choices in each country for the transportation of goods by sea. Container is a container that is specially designed with a certain size, can be used repeatedly, used to store and simultaneously transport the cargo in it. Therefore, the author took the theme of designing container ship 7200 DWT as a means of transporting coffee beans from Malahayati Port to Tanjung Priok Port. The author takes two ship data as a comparison whose results become the main value of the ship's design.